PENANDA KUALITAS MEWUJUD ADJEKTIVA SEBAGAI IDEOLOGI DALAM WACANA IKLAN ADVERTORIAL MEDIA MASSA CETAK - Nurhusna Nurhusna (Universitas Negeri Makassar, 2017)
Abstract. Quality markers Adjective manifests as Ideology in Discourse Advertorial Print Mass Media. This study used a qualitative approach with a theoretical orientation model of semiotics. This research data in the form of verbal and nonverbal words as context underlying the emergence of ideological discourse advertorial print media advertising. The data source of this research is Kompas and Jawa Pos edition of November to December 2014. The results showed that the mark of quality embodied in the discourse of advertising advertorial adjective found (1) marker adjective physical characteristics and (2) the physical characteristics apparent adjective marker. (1) marker adjective physical characteristics in the form of (a) the nature of the circumstances, (b) the nature of color, (c) the nature of the measure, (d) the nature of the form, (e) the nature distance, (f) the nature of time, and (g) the nature of the way , (2) a marker adjective physical characteristics apparent in the form of (a) the nature of the senses, and (b) the nature of feeling. Based on the research results, it is recommended to educators should be able to prepare human resources who can absorb critical information so superior, competent and proficient in the use of information; for the community should be a critical reader to absorb the intention in the discourse of advertising advertorial; advertisers should express an honest system of signs; and for further research to assess the advertorial ads from another aspect.